Visible Light Photocatalytic Activity of Ag/WO3 Nanoparticles and its Antibacterial Activity Under Ambient Light and in The Dark - Maha Matalkeh (17148358) (2022)
Nanomaterial such as metals and metal oxide photocatalysts have emerged as important tools for removing contaminants from wastewater and as antibacterial agents to prevent infections; this is mainly due to their stability under different irradiation conditions. Herein, the catalytic and antimicrobial activities of nanocrystalline silver (Ag), supported on tungsten oxide (WO3) nanoparticles prepared using the deposition-precipitation synthesis technique, are studied. The synthesized material was characterized as XRD, XPS, TEM, and TEM-EDS to investigate their physio-chemical properties. HRTEM, XPS analysis shows that the photocatalyst has a large sheet-like morphology with well-dispersed small metallic Ag particles (<3 nm) on the WO3 nanoparticle's surface, with most particles near the edges. Ultraviolet–visible spectra analysis observed a large redshift in the absorbing band edge and decreased bandgap energy from 2.6 to 2.1 eV. Photocatalytic analysis at different concentrations of 1% Ag/WO3 under visible light indicated a high degradation efficiency. The largest degradation efficiency of Methylene Blue (MB) under visible light irradiation was (∼80%) in 120 min at 1 g/L catalyst dosage. The photodegradation of MB under visible light as a function of catalyst dose followed the pseudo-first-order kinetics. In addition, the catalyst shows high degradation efficiency and significant dose-dependent inhibition of Gram-negative E. Coli and the Gram-positive S. aureus. Furthermore, the catalyst showed excellent stability and recyclability. Other Information Published in: Results in Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rineng.2021.100313 Additional institutions affiliated with: Liberal Arts and Science - VCUarts Qatar